On the mechanism of water oxidation catalyzed by a dinuclear ruthenium complex: a quantum chemical study. Issue 13 (16th March 2016) - Liao, Rong-Zhen; Kärkäs, Markus D.; Laine, Tanja M.; Åkermark, Björn; Siegbahn, Per E. M.
Abstract : The development of efficient and robust catalysts for water oxidation is an essential element in solar water splitting. In the present paper, the reaction mechanism for a dinuclear Ru water oxidation catalyst has been investigated in detail through quantum chemical calculations. Abstract : The development of efficient and robust catalysts for H2 O oxidation is an essential element in solar water splitting. The reaction mechanism for a previously reported dinuclear Ru water oxidation catalyst (1 ) has been investigated in detail through quantum chemical calculations. The predicted mechanism starts from a Ru2 III, III complex with two aqua ligands. After three sequential oxidations, O–O bond formation occurs at a formal Ru2 IV, V state via the direct coupling of two adjacent oxo moieties while the water nucleophilic attack mechanism was found to be associated with a higher energy barrier. Two H2 O molecules are then inserted with subsequent release of O2, which was found to be the rate-limiting step with a barrier of 22.7 kcal mol −1 . In a previous work, it was revealed that the ligand scaffold in the studied Ru complex has a non-innocent function. Here, we further highlight this behavior, where the ligand was shown to mediate proton transfer events and accept/donate electrons during the catalytic cycle, which can significantly decrease the redox potentials and facilitate the access to high-valent redox states. This study provides further insight into the H2 O oxidation mechanism and principles for designing improved catalysts for activation of small molecules, such as H2 O.